Influence of Compatibilization and Internal Lubricant on the Mechanical and Thermo-mechanical Properties of PLA/TPU Compound - Avci, Ali; Eker, Aysegul Akdogan; Bodur, Mehmet Safa (POLYMER SOC KOREA, 2022)
The purpose of the study is to investigate the influences of internal lubricant and maleic anhydride (MA) on tensile, flexural, toughness properties and thermal properties of brittle biopolymer polylactic (PLA), in order to consider PLA for automotive applications as a matrix material. For this aim, polylactic acid and thermoplastic polyurethane (TPU) were compounded to overcome the inherent brittleness of PLA. Three different compound types, namely PLA/TPU, PLA/MA/TPU and PLA/M/TPU/internal lubricant, were prepared by extrusion and injection processes. The influence of the internal lubricant and the coupling agent on the compounds was examined in terms of the thermal, mechanical and thermomechanical properties of the compounds. The results show that the internal lubricant could be also incorporated into PLA/TPU compounds to enhance the elongation at the break by about 16% and to improve the storage modulus of the compounds. The compatibilizer showed a significant improvement in the thermal, thermo-mechanical and mechanical properties of the compounds.
Keywords: poly(lactic acid); thermo-mechanical properties; internal lubricant; polymer compounds; MALEIC-ANHYDRIDE; CRYSTALLIZATION BEHAVIOR; RHEOLOGICAL PROPERTIES; THERMAL-PROPERTIES; COMPOSITES; MORPHOLOGY; BLENDS; PLA; POLYLACTIDE; Polymer Science